MEMBEDAH DIALOG ACARA DUA SISI “UU ORMAS MENCIDERAInDEMOKRASI?” DENGAN TEORI BREAK DAN PENDEKATAN LINGUISTIK FORENSIK: KAJIAN POLITIK HUKUM - Astuty; Susilowati, Tri (Cattleya Darmaya Fortuna, 2024)
A crime is not just a physical force, it will still be a crime can also be done through language. Forensic linguistics is a language science that analyzes crime in terms of what criminals are used. the research in this article discusses a two-sided event with the theme of